Craft Beer Tourism Development "Down Under": Perspectives of Two Stakeholder Groups. Issue 4 (2nd October 2017) - Duarte Alonso, Abel; Alexander, Nevil
ABSTRACT: This exploratory study investigates the perceived potential of craft beer tourism (CBT) in Australia, focusing on two important stakeholder groups, commercial and hobby craft brewers, and adopting stakeholder theory (ST). The importance of these stakeholders is primarily illustrated through several forms of CBT development, and perceived challenges. Fundamentally, beer tours, trails, festivals, and combining CBT with other leisure activities emerged as key forms of CBT. Geographic distance, excise taxes, price, and government regulations are the main identified challenges. Associations between the various ST-related theses and the study's findings are revealed, particularly regarding collaborative efforts to maximise perceived opportunities.